Marketing Strategy for Tourism Potential in the Framework of Regional Development as a Tourist Destination - Adam, Muhammad; Putra, Teuku Roli Ilhamsyah; Ibrahim, Mahdani (Heca Sentra Analitika, 2023)
This study discusses the marketing strategy for leveraging the tourism potential of Aceh Province, Indonesia, with the aim of developing the region into a thriving tourist destination. The respondents who participated in the survey included 200 foreign tourists and 100 domestic tourists. The data was tested and verified using Structural Equation Modeling (SEM). The primary data collected in the field indicates that, on the whole, the variables related to the research are still above the average. The results also reveal that the marketing strategy does not significantly impact the attractiveness of tourism in Aceh Province. However, when examining individual constructs within the marketing strategy model, it becomes evident that some of them positively and significantly contribute to the formation of certain dimensions of the marketing strategy, even though they may not have a statistically significant effect on tourism attractiveness. Furthermore, tourism attraction has been found to have a positive and significant impact on the excellence of tourism in Aceh Province. Tourists perceive all the tourist destinations within Aceh Province as highly superior and competitive when compared to destinations in other regions. As a result, the excellence of tourism, as highlighted in this study, is a direct outcome of tourism attractiveness, which encompasses main attractions (uniqueness), natural landscapes, cultural attractions, and traditional handicrafts.